Energy requirements in preschool-age children with cerebral palsy - Walker, J.; Bell, K.; Boyd, Roslyn; Davies, P. (2012)
Background: There is a paucity of data concerning the energy requirements (ERs) of preschool-age children with cerebral palsy (CP), the knowledge of which is essential for early nutritional management. Objective: We aimed to determine the ERs for preschool-age children with CP in relation to functional ability, motor type, and distribution and compared with typically developing children (TDC) and published estimation equations. Design: Thirty-two children with CP (63% male) of all functional abilities, motor types, and distributions and 16 TDC (63% male) aged 2.9-4.4 y participated in this study. The doubly labeled water method was used to determine ERs. Statistical analyses were conducted by 1-factor ANOVA and post hoc Tukey honestly significant difference tests, independent and paired t tests, Bland and Altman analyses, correlations, and multivariable regressions. Results: As a population, children with CP had significantly lower ERs than did TDC (P < 0.05). No significant difference in ERs was found between ambulant children and TDC. Marginally ambulant and nonambulant children had ERs that were ~18% lower than those of ambulant children and 31% lower than those of TDC. A trend toward lower ERs with greater numbers of limbs involved was observed. The influence of motor type could not be determined statistically. Published equations substantially underestimated ERs in the nonambulant children by ~22%. Conclusions: In preschool-age children with CP, ERs decreased as ambulatory status declined and more limbs were involved. The greatest predictor of ERs was fat-free mass, then ambulatory status. Future research should build on the information presented to expand the knowledge base regarding ERs in children with CP. This trial was registered with the Australian New Zealand Clinical Trials Registry as ACTRN 12612000686808. © 2012 American Society for Nutrition.